Ethics of Learners in the Book of Ma’ālim Fī Ṭarīq Ṭalab Al-’Ilm by Sheikh ‘Abd Al-’Azīz As-Sadhān (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to analyze the ethics of learners from the perspective of Sheikh ‘Abd al-’Azīz as-Sadhān in the book Ma’ālim fī Ṭarīq Ṭalab al ‘Ilm and analyze the relevance of the ethics of learners from the perspective of Sheikh ‘Abd al-’Azīz as-Sadhān in the book Ma’ālim fī Ṭarīq Ṭalab al-’Ilm in the current context. This type of research is qualitative research with a library research approach. The data analysis technique uses content analysis technique. The results of this study globally include Shaykh ‘Abd al-’Azīz as-Sadhān’s thoughts on student ethics. The classification includes the ethics of students when seeking knowledge 19 ethics, ethics of students towards themselves 4 ethics, ethics of students when in the mosque 3 ethics, ethics of students when at home 3 ethics, ethics of students with peers 9 ethics, ethics of students in the midst of society 13 ethics, ethics of students buying books and owning them 11 ethics, ethics of students borrowing books 9 ethics, ethics of students towards the Qur’an 7 ethics, ethics of students when accommodating information 2 ethics, ethics of students praying at night 3 ethics, ethics of students devoted to parents only 1 ethics, ethics of students in scientific debates 8 ethics, and ethics of students in the macro scope 31 ethics.